THE EXPERTS’ VIEWS ON FACTORS INFLUENCING THE EFFECTIVE IMPLEMENTATION OF STATUTORY ADJUDICATION - Modupe MEWOMO; Marthinus MARITZ (Journal of Construction Project Management and Innovation)
The fundamental drive behind the introduction of the statutory adjudication scheme is to improve cash flow within the construction industry and also to provide a swift and inexpensive means of resolving construction disputes. While cash flow is widely regarded as the lifeblood of the construction industry, unfair payment practices remain a lingering issue affecting the delivery chain. Most often, contractors and subcontractors at the lower rung of the contractual chain face financial difficulties from main contractors who delay or refuse payment in the knowledge that court and arbitration proceedings are often too expensive and a slow remedy for the smaller contractors in particular. These oppressive acts, in many instances, have led to insolvency of the lower-chain players and, as such, generated serious concerns within the construction industry. Consequently, statutory adjudication was introduced in several countries globally to offer swift relief to the financially squeezed and cash-starved (sub)contractors. Similar legislation is about to be promulgated in the South African (SA) construction industry. This paper details the experts’ views on critical factors that can enhance the effective implementation of the statutory adjudication process in SA. Data were gathered through qualitative interviews with fifteen adjudication experts that have direct interaction with profound knowledge of the adjudication process in the United Kingdom (UK), Australia, Singapore and Malaysia. The findings reveal the influencing factors in the form of combinations of ‘enablers’ and ‘drivers’ upon which successful implementation of statutory adjudication and the realisation of the benefits it has to offer could be hinged.